Women in Christian Substance Abuse Treatment; Forgiveness, Attachment Styles, and Improvements in Co-occurring Mental Health Symptoms - Kerlin, Ann Marie (Journal of religion and health, 2020)
The purpose of this study was to explore the efficacy of The Recovery Center at Shalom House Ministries and examine the relationship(s) between forgiveness, attachment styles, drug and alcohol abuse, self-reported mental health symptoms, and cognitive functioning. Participants (N = 118 women) attended Shalom Recovery (2016-2018). Statistically significant improvement was found between entrance and the 3-month mark on all measures, with 67.9% completing the program. Findings indicated that the revenge motivations correlated with depression, self-esteem, anxiety, and avoidance of intimacy with God, but only this latter scale contributed to a multiple regression model on revenge motivations at program entry.